The Effects of Funding on Student Performance: Findings from PISA 2018 - Gabriella Szekeres (Vancza); Alina Caldararu; Mihai Paunica (Journal of Accounting and Management Information Systems (JAMIS), 2021)
Research Question - Is there a link between the investment in human capital, measured by the average gross salary in the pre-university education system and the student-teacher ratio together with the results obtained by students in tests? Motivation - In any society, the work done by man to obtain results is always present. Human capital in the economic and accounting context cannot be dissociated from its cost, and in the public system, it acquires an even greater influence. The role of human capital and implicitly its cost in the public expenditure system represents the largest part, and its significance is accentuated in education. Idea - The authors of this paper tried to see if investing in human capital has positive consequences on the outcome of the pre-university education system. Data - Research data were collected from the OECD (Organization for Economic Co-operation and Development) website Tools - The research was performed by quantitative methods using the least squares regression equation. The hypotheses tested by the authors were the existence of a relevant positive or negative correlation between the indicators presented. Findings - Following the analysis, found that there was a positive correlation between the salary level indicators and the average score obtained in tests, and a negative correlation between the number of students per teacher and test results. Contribution - This paper contributes to research in the field on the effects of decisions regarding funding and pay policy for pre-university education using the results obtained by students in standardized tests. Therefore, this research is part of a larger research project that shows that the level of funding is correlated with the results of students measured by tests in pre-university education.
Keywords: H52; P44; P43; H61; I22; M48; H75; 650; salary costs in the education system; PISA tests; number of students per teacher; financing in education